The impact of fetal umbilical artery Doppler pulsatility index on childhood respiratory function and atopy: a prospective case-control study. (3rd March 2020) - Mone, Fionnuala; Thompson, Andrew; Stewart, Moira C.; Segurado, Ricardo; Curry, Jennifer; Dornan, James C.; McAuliffe, Fionnuala M.; Shields, Michael D.
Abstract: Objective: To determine if an elevated fetal umbilical artery Doppler pulsatility index is associated with abnormal respiratory function and atopy in children aged 12 years. Methods: This prospective case-control study compared children that had an elevated fetal umbilical artery Doppler pulsatility index (>90th centile) to those with a normal pulsatility index (<90th centile). All subjects were delivered at full-term and with appropriate growth for gestational age. Outcome measures included; (i) presence of asthma and/or atopy; (ii) spirometry measurements and (iii) serum C-reactive protein and leptin. Multiple regression was used to account for parental smoking, childhood age, gender and socioeconomic status. Results: 174 children with an average age of 12.1 (±0.6 SD), 48% of who were male were included in the analysis. Of the 174, 99 (57%) were in the normal umbilical artery Doppler pulsatility index group and 75 (43%) elevated umbilical artery Doppler pulsatility index groups. The overall proportion of subjects with asthma was 28% (48/174) and atopy 56% (98/174). No association was found between elevated fetal umbilical artery Doppler pulsatility index and asthma ( p = .47) or atopy ( p = .75) at age 12 years. Similarly there was no association between FEV1(%) ( p = .96), forced vital capacity (FVC)(%) ( p = .98), elevated serum C-reactive protein ( p = .69) or leptin ( p = .20) and an elevated fetal umbilical artery Doppler pulsatility index. Conclusions: An elevated umbilical artery Doppler at 28-weeks gestation in the absence of prematurity or fetal growth restriction is not associated with altered respiratory function or the presence of atopy in children aged 12 years. These findings support the theory that such disease has a multifactorial pathophysiology.